Evaluation of two aneuploidy screening tests for chorionic villus samples: Multiplex ligation-dependent probe amplification and fluorescence in situ hybridization. (August 2019) - Wu, Tonghua; Zhu, Yuanchang; Hong, Ling; Lin, Qi; Chen, Chunmei; Yang, Jing; Ye, Lijun; Huang, Wensi; Zeng, Yong
Abstract: The vast majority of first-trimester pregnancy losses are the consequence of numerical aberrations in fetal chromosomes, which may involve nearly all chromosomes. Although commercial probes for all chromosomes are available for multiplex ligation-dependent probe amplification (MLPA) and fluorescence in situ hybridization (FISH) analyses, their use has rarely been reported for screening all 24 chromosomes for early fetal demise, especially by FISH. Here, we validated the ability of MLPA and FISH techniques as two low-cost aneuploidy screening methods for 24 chromosomes in 165 chorionic villus samples (CVSs). The results obtained by two methods were compared by the Chi-square test and the Kappa agreement test. Both methods gave conclusive results for all CVSs tested and showed highly consistent results (kappa = 0.890, p  < 0.001). There was no statistically significant difference between the aneuploidy rate of the CVSs tested by the two methods ( p  = 0.180). Most of the samples showed fully concordant molecular karyotyping results (81.21%) between the two analytical methods, 10.91% had incompletely concordant results, and 7.88% had discordant results. The inconsistencies included segmental abnormalities, mosaicism, and polyploidy. Both assays used to screen 24 chromosomes were powerful techniques for detecting aneuploidy in CVSs. In terms of cost-effectiveness and diagnostic accuracy, the combination of subtelomeric (P036, P070) and centromeric (P181) MLPA assays is the better analytic strategy and follow-up analysis by FISH is recommended for MLPA-negative samples. Highlights: Results of MLPA and FISH screening for 24 chromosomes on CVSs showed highly consistent. Inconsistencies included segmental abnormality, mosaicism and polyploidy. Most of FCAs can be discerned by MLPA method with a lower cost and an easier workflow. Combination of subtelomeric and subcentromeric MLPA assays is the preferred strategy for aneuploidy detection in CVSs. FISH is recommended as a supplementary examination on MLPA-negative samples.